2022
DOI: 10.1007/s10071-022-01689-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of repeated testing on judgement bias in domestic dogs (Canis familiaris)

Abstract: Judgement bias paradigms are increasingly being used as a measure of affective state in dogs. Approach to an ambiguous stimulus is commonly used as a measure of affect, however, this may also be influenced by learning. This study directly measured the impact of learning on a commonly used judgement bias paradigm in the absence of an affective state manipulation. Dogs (N = 15) were tested on a judgement bias task across five sessions. The dogs’ latency to approach a bowl placed in one of three ambiguous locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…These ndings suggest a learning effect that may have occurred due to our repeated testing design. This effect has previously been shown to occur in sheep 76 and in dogs 77 where Wilson et al (2023), found that repeated cognitive bias testing (up to ve sessions) resulted in an increase in latency to approach ambiguous locations and a decrease in the number of approaches. This is likely due to animals learning that the ambiguous locations are not rewarded, and therefore beginning to treat them as negative cues.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…These ndings suggest a learning effect that may have occurred due to our repeated testing design. This effect has previously been shown to occur in sheep 76 and in dogs 77 where Wilson et al (2023), found that repeated cognitive bias testing (up to ve sessions) resulted in an increase in latency to approach ambiguous locations and a decrease in the number of approaches. This is likely due to animals learning that the ambiguous locations are not rewarded, and therefore beginning to treat them as negative cues.…”
Section: Discussionmentioning
confidence: 62%
“…Although we observed a signi cant decrease in the likelihood of approaching NN between baseline and session 3, we did not see a decrease in the likelihood of approaching between baseline and session 2 or between session 2 and 3. Neither did we see a signi cant effect of session at the NP or M locations as observed by Wilson et al (2023) 77 , suggesting our modi cation may have been effective at minimising learning effects at these two ambiguous locations. Although the effects at N and P were not reported by Wilson et al (2023), the signi cant decrease in likelihood of approaching N and the signi cant increaseinlikelihood of approaching P between session 1, 2 and 3 in the current study is likely also due to a learning effect.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…This outcome is consistent with several studies that have indicated that the impact of learning on animals’ responses to ambiguous stimuli can represent a significant confounding factor that affects the interpretation of results from judgment bias tests. 19 , 26 , 27 It is worth mentioning that we detected a learning effect despite having reduced the ratio of ambiguous stimulus trials relative to reference stimulus trials in each session (274:10) and having implemented a variable reinforcement schedule (80%) following prior research. 19 , 20 , 28 Nevertheless, despite the learning effect, the tendency for response times to be prolonged in the snake condition relative to the control condition was persistent even in later trials, as depicted in Figure 3 .…”
Section: Discussionmentioning
confidence: 71%